IT governance evaluation at the population and civil registry office in Kolaka district using COBIT 5 framework - Zainuddin, Noorhasanah; Winarno, Wing Wahyu; Ningsi, Nurfitria; Pasrun, Yuwanda Purnamasari; Muliyadi, Muliyadi (Information Systems - Universitas Pesantren Tinggi Darul Ulum, 2020)
The implementation of information technology is compulsory to fit organizational goals. This research aims to evaluate the quality of information technology services at the Population and Civil Registry Office at Kolaka District based on COBIT 5 Framework that focused on DSS (deliver, service and support) domain by measuring the Maturity Level using Process Assessment Model (PAM). The Population and Civil Registry Office is under the local government ‘s auspices which is essential in managing the population. The data collection method was done by distributing questionnaires and conducting interviews. This study used 8 (eight) respondents based on the RACI chart. This research was expected to reach level 3 (established process) to create IT governance that fits organizational goals and international standards. From the research result, it is known that the maturity level from the evaluation process conducted by COBIT 5 using the processes DSS-01, DSS-02, DSS-03, DSS-04, DSS-05, and DSS-06 were as follows: 2 processes were at level 1 (performed process), namely the DSS-05 and DSS-06 while the others (DSS-01, DSS-02, DSS-03, and DSS-04) were at level 2 (managed process).